Identifying and evaluating important factors which cause Onset End-Stage Renal Disease in Al-Marj City in the period from August 2023 to January 2024 - Rabeaa Mohammad Saleh; Najwa Ayad Saad Al-Aqili; Nessrin Abd-Alrihem Suliman (African Journal of Advanced Pure and Applied Sciences, 2024)
The present study aimed to identify and evaluate the important factors which cause the rise in the onset of ESRD, which demands hemodialysis in Al-Marj city. The present study was conducted at Dialysis Center at Al-Marj Educational Hospital. The data was collected by using a questionnaire with 80 patients, The ages of the participants (20 years to 60 years). These Data were collected during the period from August 2023 to January 2024. Data in the questionnaire were analyzed using the software program Statistical Package for Social Sciences (SPSS).In the present study the important factors associated with the onset of ESRD: are diabetes mellitus, hypertension, cardiovascular disease, recurrent analgesic drug, BMI, and infection of urinary tract. The result showed that there were no significant effects of gender, age and smoking on the onset of ESRD.